Konstruksi Identitas Melanesia Negara-Negara Pasifik Selatan dan Respons Indonesia terkait Papua - Aulia Namira Hasibuan; Christopher Sebastian Simanjuntak; Razanul Hariz Habiburrahman; Deasy Silvya Sari; Dina Yulianti (Journal Social Politica, 2026)
The Papua issue has become one of the prominent topics in Indonesia’s relations with  South Pacific countries, particularly due to the shared Melanesian identity between Papuans and many communities in the region. The expansion of digital media has further facilitated the dissemination of narratives surrounding Papua through news coverage, political statements, and international forums, shaping both regional and global public perceptions. This study aims to explain how Melanesian identity is constructed within the digital discourse of South Pacific countries regarding Papua and how Indonesia responds to such identity construction through its diplomatic approaches. This research employs a qualitative approach using a library research method. Data were collected from books, scholarly journals, official documents, institutional reports, and relevant online publications. The analysis utilizes the concept of Political Netnography developed by Robert V. Kozinets and Rossella Gambetti to examine patterns of interaction, narratives, symbols, and the formation of political identities within digital spaces. The findings reveal that Melanesian identity in the digital discourse of South Pacific countries is constructed as a foundation for solidarity with Papua through narratives of human rights, decolonization, and ethnocultural affinity. These narratives are continuously reproduced through online media and international forums, including the United Nations and the Melanesian Spearhead Group. In response, Indonesia employs formal diplomacy, exercises its right of reply in international forums, strengthens cooperation with South Pacific countries, and promotes counter-narratives emphasizing sovereignty, territorial integrity, and development in Papua. The study concludes that the contestation of narratives regarding Papua takes place not only in formal diplomatic arenas but also in digital spaces that play a significant role in shaping collective identities, public opinion, and international perceptions of Papua and Indonesia.